2010
DOI: 10.1002/jso.21538
|View full text |Cite
|
Sign up to set email alerts
|

ALCAM is associated with chemoresistance and tumor cell adhesion in pancreatic cancer

Abstract: We propose ALCAM as a novel serum biomarker in human pancreatic tumors which is associated with cell adhesion, growth and chemoresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 34 publications
6
40
1
Order By: Relevance
“…Hong and colleagues recently described a prognostic effect of ALCAM in PNET, but did not substantiate this with results or details in their manuscript [21]. Nevertheless, they performed in vitro ALCAM RNAi experiments in their study with a PNET cell line (BON), and observed a significant reduction in the proliferative activity of the tumor cells, which is in clear contrast to our immunohistochemical findings.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Hong and colleagues recently described a prognostic effect of ALCAM in PNET, but did not substantiate this with results or details in their manuscript [21]. Nevertheless, they performed in vitro ALCAM RNAi experiments in their study with a PNET cell line (BON), and observed a significant reduction in the proliferative activity of the tumor cells, which is in clear contrast to our immunohistochemical findings.…”
Section: Discussioncontrasting
confidence: 87%
“…This ambiguity is very clear in the oppositional effect of ALCAM in neuroendocrine tumors and adenocarcinoma of the pancreas. A high expression of ALCAM is reported to be associated with a poor prognosis for patients with pancreatic adenocarcinoma [11,21]. As a consequence, it is highly unlikely that ALCAM functions as a receptor for metastatic deor attachment in the same primary or metastatic host tissue, but it might play a regulatory role in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD166 is involved in hematopoiesis (19,20), neurite extension (21), osteogenesis (22), and embryonic implantation in the uterus (23). The level of CD166 expression correlates with the aggregation and metastatic potential of a few human tumors (24), including melanoma (25,26) and prostate (27,28), ovarian (29), breast (30 -32), colorectal (33,34), esophageal (35), and pancreatic cancer (36,37). Furthermore, AL-CAM was also identified in medium conditioned by breast cancer cells and may be a potential serum breast cancer biomarker (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies report altered serum levels in pancreatic cancer [21] and ovarian cancer [22] but make no statement about its prognostic value. To our knowledge, we are the first to note that high sALCAM levels are a predictor of shorter DFS in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%